O que é o inglês para turismo? - Martins, Patrícia de Oliveira (2016)
This work aims to explore English teaching in the Vocational School and its adequacy to the world of work, more specifically during the third year students’ traineeship in the Professional Course of Tourism Technicians. Through questionnaires it was possible to outline the students’ expectations and evaluate their opinions about the topics taught in the curricula and their usefulness and effective use in the world of work. It is important to refer the cooperation of the Professional School of Espinho, its students and the tutors and institutions where the students made their training for the development of this project and to conclude that the curricula can still be adapted and enriched in this professional area.